2017
DOI: 10.1016/j.celrep.2017.05.033
|View full text |Cite
|
Sign up to set email alerts
|

Sonic Hedgehog Activates Phospholipase A2 to Enhance Smoothened Ciliary Translocation

Abstract: Summary The G protein-coupled receptor Smoothened (Smo) is the signal transducer of the Sonic Hedgehog (Shh) pathway. Smo signals through G protein-dependent and independent routes, with G protein-independent canonical signaling to Gli effectors requiring Smo accumulation in the primary cilium. Mechanisms controlling Smo activation and trafficking are not yet clear, but likely entail small-molecule binding to pockets in its extracellular cysteine-rich domain (CRD) and/or transmembrane bundle. Herein we demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 55 publications
4
35
0
Order By: Relevance
“…Cell viability was then measured with the CCK8 assay. The in vitro experiments were conducted using the following four groups: (a) NC group, LX2 cells without any treatment; (b‐d) L, M and H groups, respectively, LX2 cells were treated with 60, 80 and 100 μM PB2, respectively; (e) cyclopamine group, LX2 cells were treated with 10 μM cyclopamine; and (f) PB2 (M) + SAG group, LX2 cells were treated with 100 nM SAG . All of the experiments were performed in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Cell viability was then measured with the CCK8 assay. The in vitro experiments were conducted using the following four groups: (a) NC group, LX2 cells without any treatment; (b‐d) L, M and H groups, respectively, LX2 cells were treated with 60, 80 and 100 μM PB2, respectively; (e) cyclopamine group, LX2 cells were treated with 10 μM cyclopamine; and (f) PB2 (M) + SAG group, LX2 cells were treated with 100 nM SAG . All of the experiments were performed in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Gαi involvement is further supported by the observation that metabolism of arachidonic acid through the 5-lipoxygenase pathway contributes to fibroblast chemotaxis [ 44 ]. We recently demonstrated that Smo signaling through Gαiβγ activates the lipid remodeling enzyme cPLA2α to produce arachidonic acid [ 18 ], providing a mechanism by which the free fatty acid would be made available for lipoxygenase activity.…”
Section: Cytoskeletal Dynamics Cellular Migration and Axon Guidamentioning
confidence: 99%
“…However, increasing cAMP levels in pre-adipocytes in vitro can rescue adipocyte differentiation in the presence of excessive Shh signaling [ 70 , 72 ], raising the possibility that a Smo-Gαi-cAMP signal axis may be capable of influencing adipocyte differentiation in coordination with canonical Smo signaling activity. The ability of the noncanonical arm to influence the canonical arm through Gαi activation is feasible; we recently reported that arachidonic acid produced in response to Smo signaling through Gαiβγ directly associates with Smo to promote its ciliary entry and enhance signaling to Gli [ 18 ]. As such, activation of the noncanonical arm may function to amplify canonical signaling in select cell types during cell fate specification and tissue morphogenesis.…”
Section: Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Das et al 2013;Touster et al 1970;Colbeau, Nachbaur, and Vignais 1971) : how can such an abundant lipid be kept away from SMO to prevent inappropriate pathway activation? Indeed, other less abundant lipids can bind and regulate SMO activity, including oxysterols, phosphoinositides, endocannabinoids and arachidonic acid derivatives (Nachtergaele et al 2012;Khaliullina et al 2015;Arensdorf et al 2017;Jiang et al 2016) . Side-chain oxysterols, synthesized through the enzymatic or non-enzymatic oxidation of cholesterol, are appealing alternatives to cholesterol because of their lower abundance, higher hydrophilicity and structural similarity to cholesterol (Corcoran and Scott 2006;Dwyer et al 2007) .…”
Section: Introductionmentioning
confidence: 99%